Analisis Faktor-Faktor yang Memengaruhi Kepatuhan Minum Obat pada Penderita DM Tipe 2 di Wilayah Kerja Puskesmas Muarasoma Tahun 2021 - Dalimunthe, Puput Novianty; Sipayung, Novreka Pratiwi; Sitanggang, Ervina Julien; Zaluchu, Ristarin Paskarina (Universitas HKBP Nommensen, 2023)
Abstract Background : Type 2 DM is DM with hyperglycemia due to a combination of insulin action resistance, insulin secretion and excessive or inadequate glucagon secretion. High adherence to medication is one of the factors that determine the success of the DM type 2 control process. Objective : This study aimed to analyze the factors that influence adherence to taking antidiabetic drugs in the Muarasoma Health Center Work Area in 2021. Methods: This study is an analytical study using a cross-sectional approach which was conducted on 77 patientswith type 2 DM according to the inclusion and exclusion criteria in the working area of the Muarasoma HealthCenter. Knowledge level, medication adherence and family support were measured using the Diabetes Knowledge Quiestionnaire (DKQ-24), Morisky Medication Adherence Scale (MMAS-8) and the Hensarling Diabetes Family Support (HDFS) which have been validated. Results: The factors influencing medication adherence in patients with type 2 DM were gender with p value = 0,002), education level with p value = 0,007, income with p value = 0,015, level of knowledge with p value =0,047, and family support with p value = 0,043). Factors that are not associated with medication adherence in patients with type 2 DM were DM duration with p value = 0,059 and drug regimen with p value = 0,056 Conclusion: The factors that influence medication adherence in patients with type 2 DM at the Muarasoma Health Center are gender, level of education, level of knowledge, income, and family support.